ANALISIS PENGEMBANGAN USAHA DENGAN SISTEM WARALABA PADA USAHA KULINER BEBEK MADURA BEMA - Zaki Akbar Anwariansyah; Nur Widiastuti; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The growth of interest in business, especially in the culinary, opens up opportunities to develop a business with a franchise system. This study aims to analyze business development and the efforts of culinary business owner with a franchise system. A franchise or franchising is a method of distributing products or services involving a franchisor, who establishes the brand trademark or trade name and a business system, and a franchisee, who pays a royalty and often an initial fee for the right to do business under the franchisor name and system based on franchise agreements. The research was conducted on a culinary company named BeMa Bebek Madura which has applying franchise system. This study uses a qualitative descriptive method by conducting analysis through data reduction, data presentation and drawing conclusions. The results of the research show that there are two types of franchise systems, pure franchising and product distribution franchising. There is an analysis of business criteria that run a franchise system. Business owners in running a franchise system make various efforts since the franchise agreement will be implemented until the business runs to ensure the business runs well.